The impact of vertical jump height, hamstrings flexibility and strength on maximal sprint speed in Division I track and field athletes - Doyle, K. P.; Brinken, C. M.; Capito, C. N.; Karp, E. T.; Mariani, M. N.; Meza, S.; Grimes, J. K. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this study was to examine the relationship between hamstrings flexibility, eccentric strength, and vertical jump height with maximal sprint speed (MSS) in collegiate Division 1 track and field athletes. The impact of previous hamstrings injury was also investigated in an exploratory secondary analysis. The 90/90 active knee extension test was used to examine flexibility of the hamstrings. Vertical jump height was assessed as an indicator of lower extremity power. Eccentric peak torque of the hamstrings was assessed with isokinetic dynamometry at 60°/s-1. Maximal sprint speed was measured over a 60-meter distance by taking the fastest 10-meter flying split using electronic timing gates. The level of significance was set at p < 0.05. Vertical jump height had a significant strong positive correlation (r = 0.74; p < 0.001) with MSS. Hamstrings flexibility on the right had a significant weak negative correlation (r = -0.37; p = 0.03) with MSS. No significant correlations were found between hamstrings flexibility on the left (r = -0.20; p = 0.26) or eccentric normalized peak torque (right: r = 0.15; p = 0.40; left: r = 0.27; p = 0.13) and MSS. Vertical jump height demonstrated the strongest correlation with MSS. When comparing those with and without previous hamstrings injury, vertical jump height (mean 67.5 vs. 55.1 cm; p = 0.062) may have clinical importance and should be examined in a larger sample with previous hamstring injury. Understanding how the hamstrings adapt to sprint-specific training will contribute to the design and implementation of training programs in track and field athletes to improve performance.